THE ROLE OF ADIPONECTIN IN THE DEVELOPMENT AND PROGRESSION OF METABOLIC SYNDROME - Khujamberdiev M.A. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Metabolic syndrome (MS) is a complex interrelated pathogenetic symptoms and metabolic disorders that increase the risk of developing atherosclerosis and coronary heart disease (CHD) among which highlight violations such as obesity and/or abdominal fat distribution, insulin resistance (IR), atherogenic dyslipidemia, arterial hypertension (AH), hyperuricemia, and several other manifestations [2,3,5].